Preparation of ellagic acid, huppuric acid, perindopril erbumine and cetirizine nanocomposites for drug delivery - Ahmad Hussein Al Ali, Samer Hasan (2012)
The administration of drugs designed to be given as a single dose rather than multiple doses has recently been made possible using controlled release formulation approach, so that the release of the drugs can be accomplished over long periods of time, enabling an almost constant level of the drug to be maintained in the bloodstream. Moreover, controlled release formulations increase the clinical efficacy of drugs. The introduction of drug nanocomposites as sustained release vehicles has provided a breakthrough in novel drug delivery systems in the field of pharmaceutical technology. Layered double hydroxides (LDHs) are widely used for this purpose. This study aimed at the synthesis of new controlled release formulation of ellagic acid, hippuric acid, perindopril erbumine and cetirizine hydrochloric acid via intercalation of the drug either into zinc-aluminium-, magnesium-aluminium-layered double hydroxides and zinc layered hydroxide, to increase the residence time in the body by sustained release and therefore increase the clinical efficacy. Eighth nanocomposites were synthesized using zinc layered hydroxide, zinc-aluminium- and magnesium-aluminium-layered double hydroxides. Ellagic acid and hippuric acid were intercalated into zinc layered hydroxides to form ellagic acid, hippuric acid nanocomposites; EAN and HAN, respectively. Perindopril erbumine was also intercalated into zinc-aluminium-layered double hydroxides to form PZAC and PZAE nanocomposites by direct- and ion exchange-method, respectively. In addition, this drug was also intercalated into magnesium-aluminium-layered double hydroxides to form PMAN nanocomposite. In addition, cetirizine was intercalated into zinc layerd hydroxide, zinc-aluminium-layered double hydroxide and magnesium-aluminium-layered double hydroxide to form CETN, CTZAN and CTMAN nanocomposite, respectively. The basal spacing for the nanocomposite is 10.4, 21.3, 21.7, 19.9, 21.98, 33.9, 31.9 and 31.2 Å for EAN, HAN, PZAE, PZAC, PMAE, CETN, CTZAN and CTMAN , respectively. The result coupled with molecular geometry calculation indicate that the spatial orientation of the drugs in the layered inorganic sheets was monolayer for EAN, HAN and PZAC nanocomposites; and as bilayers for PZAE, PMAE, CETN, CTZAN and CTMAN nanocomposites. The release of the ellagic acid from its nanocomposite into aqueous solution of Na3PO4 and Na2CO3, at 38 hours was 94 % and 69 %, respectively. The release of the drugs from HAN, PZAE, PZAC, PMAE, CETN, CTZAN and CTMAN nanocomposites at pH 7.4 is 3780, 1000, 1263, 5000, 4980, 600 and 2980 minutes, respectively, compared to 1260, 1100, 1020, 1000, 4320, 600 and 750 minutes, respectively at pH 4.8. This result indicates sustained release of the drugs from their respective nanocomposites, and therefore these nanocomposites have good potential to be used as controlled-release formulation of the drugs. In vitro bioassay study for EAN nanocomposite, the result showed that EAN has a mild effect on the hepatocytes cells, similar to its counterpart, the free EA. HAN has synergistic properties with tamoxifen toward a HepG2 cells line, with an IC50 value of 0.35 compared to hippurate. In the antiproliferative assay, the ratio of viable cells account for cells treated by the combination of tamoxifen with HAN to untreated cells was sharply reduced to 66 % and 13 % after 24 and 72 hours, respectively. The angiotensin converting enzyme (ACE) inhibition activity of perindopril in PZAE, PZAC and PMAE nanocomposites was determined in vitro. The three formulations shows inhibition with 70.6, 70.1 and 55.4 % for PMAE, PZAE and PZAC nanocomposites, respectively. The MgAl-LDH shows mild potent ACE inhibitory activity with 5.6 % decreased in ACE activity, while the ZnAl-LDH did not show any effect toward ACE enzyme. Release of histamine from RBL-2H3 cells was found to be more sensitive to the intercalated cetirizine in the CETN nanocomposite compared to its free counterpart with inhibition of 56 % and 29 %, respectively at 62.5 ng/ml. The inhibition of histamine by the free cetirizine is higher than the intercalated cetirizine into CTZAN and CTMAN nanocomposites. This study showed that the formation of organic-inorganic nanocomposite materials of ellagic acid, hippuric acid, perindopril erbumine and cetirizine as organic guests and zinc-aluminium-layered double hydroxide, magnesium-aluminium-layered double hydroxides and zinc-layered hydroxide as hosts can be successfully accomplished. All the nanocomposites show controlled release property of the organic guests, the drug actives, and therefore are useful for drug delivery systems.